Experimental study of a latent heat thermal energy storage system assisted by a heat pipe network. (1st December 2017) - Tiari, Saeed; Mahdavi, Mahboobe; Qiu, Songgang
Highlights: Different operation modes of a latent heat thermal energy storage unit are studied. The thermal energy storage system is assisted by a heat pipe network. The effects of heat transfer fluid flow rate and temperature are studied. Heat transfer fluid temperature has notable impact on both charging and discharging. Discharging process is hardly influenced by the heat transfer fluid flow rate. Abstract: The charging and discharging processes of a latent heat thermal energy storage system assisted by a heat pipe network was experimentally studied. Rubitherm RT55 was chosen as the phase change material (PCM) and was enclosed within a vertical cylindrical container. A network of simulated heat pipes was embedded within the PCM to enhance the heat transfer. The heat pipe array consisted of a primary central heat pipe with an array of secondary heat pipes. The primary heat pipe transfers the thermal energy from the heat source to the heat sink while the secondary heat pipes transport the extra thermal energy into to the phase change material during the charging process or retrieve it from the phase change material during the discharging process. The heat pipe network was simplified by employing an arrangement of copper and acrylic pipes. Water was used as the heat transport fluid, which was circulated through the pipe network with a relatively high velocity to decrease the temperature drop, similar to what happens inside a real heat pipe. The effects of different heat transfer fluid flow rates and temperatures on the thermal performance of the latent heat energy storage system were studied. The results indicated that the heat transfer fluid flow rate and temperature have significant impacts on the total charging time of the system. It was also found that the while the flow rate of the heat transfer fluid has minimal effect on the discharging process, the temperature of the heat transfer fluid plays a significant role.